2021
DOI: 10.1186/s12915-021-01054-9
|View full text |Cite
|
Sign up to set email alerts
|

α2β1 integrins spatially restrict Cdc42 activity to stabilise adherens junctions

Abstract: Background Keratinocytes form the main protective barrier in the skin to separate the underlying tissue from the external environment. In order to maintain this barrier, keratinocytes form robust junctions between neighbouring cells as well as with the underlying extracellular matrix. Cell–cell adhesions are mediated primarily through cadherin receptors, whereas the integrin family of transmembrane receptors is predominantly associated with assembly of matrix adhesions. Integrins have been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Both α-catenin and β-catenin have been suggested as potential interacting partners of CAR and may therefore mediate formation of this multi-protein complex ( 54 , 55 ). FAK, Src and paxillin also associate with integrins and recent work from our lab and others have shown that integrins localise to cell-cell contacts in several epithelial-like cells ( 32 , 56 , 57 ). Moreover, we show that Src activity can help to promote CAR stability at cell-cell adhesion sites, indicating formation of this complex may in turn control CAR localisation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Both α-catenin and β-catenin have been suggested as potential interacting partners of CAR and may therefore mediate formation of this multi-protein complex ( 54 , 55 ). FAK, Src and paxillin also associate with integrins and recent work from our lab and others have shown that integrins localise to cell-cell contacts in several epithelial-like cells ( 32 , 56 , 57 ). Moreover, we show that Src activity can help to promote CAR stability at cell-cell adhesion sites, indicating formation of this complex may in turn control CAR localisation.…”
Section: Discussionmentioning
confidence: 62%
“…CMT and LLC cells were treated with Ad5 FK (100μg/mL for 2.5h), FAK inhibitor (PF228; 1μM for 4h), Rap1A inhibitor (GGTI298, 10μM for 30min) or Src inhibitor (PP2, 5μM for 4h). PP2 also inhibits Lck and Fyn members of the Src family of tyrosine kinases ( 31 ) but PP2 has been previously shown to effectively inhibit Src activity ( 32 ) at concentrations used here ( 33 ). Effective inhibition of Src was proven by reduced pY418Src.…”
Section: Methodsmentioning
confidence: 93%
“…Lack of integrin expression on the apical surface is also a feature of human enterocytes, in which α 3 β 1 and α 2 β 1 integrins are found exclusively on baso-lateral surfaces (Beaulieu, 1992 ). Although their functional role is unclear, these integrins may be expressed on lateral enterocyte surfaces to establish robust intercellular connections, since the α 2 β 1 integrin was recently found to be required for stabilizing adherence junctions and barrier function in keratinocyte layers (Howden et al, 2021 ). Of note, the α 6 β 1 integrin is selectively expressed on the basal surface of all tissue enterocytes (Perreault et al, 1995 ), but was not investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Given α2β1 integrins are collagen receptors, it may be surprising that they contribute to ERK activity in inner spheroid cells, where no ECM contact is present. One explanation for this might lie in our recent discovery that active α2β1 integrins are present at epithelial cell-cell adhesions where they contribute to junction stability ( Howden et al, 2021 ), and previous studies showing colocalization between integrins and EGFR at these sites ( Yu et al, 2000 ). Whilst this has yet to be assessed in cancer cell spheroids or tumors, it is possible that integrins also have functional roles in non-ECM binding cells in our current model.…”
Section: Discussionmentioning
confidence: 99%